(untitled) - McKeague, Charles P. (Australia, 2008)
The six trigonometric functions, Right triangle trigonometry, Radian measure, Graphing and inverse funtions, Identities and formulas, Equations, Triangles, Complex numbers and polar coordinates, Review of functions, Exponential and logarithmic funtions, Answers to exercises and chapter tests, Index.
Keywords: Trigonometry,Lượng giác học